Bringing to light a new energy path: the case of the state of Minas Gerais, Brazil - Ribeiro, Ana Pimenta (Sustainability in Debate, 2023)
In Brazil, more than 55% of the energy comes from hydroelectricity, making the system highly vulnerable in the context of global climate change, with precipitation and temperature shifts over the years. Characterised by its multiple opportunities in sources and conversion technologies for energy, biomass has a high potential to become responsible for a relevant share of the renewable energy supply. Previous studies on biomass energy production in Brazil confirm promising results. This paper highlights possibilities for biomass power generation in Minas Gerais State. To estimate energy productivity, a Sustainable Technical Coefficient was adopted: a conservative index that considers the portion of residues that could be used to maintain the integrity of the soil. This index was applied with the data on silviculture and selected crop yields. The local energy demand was also calculated and compared to the potential energy production. Results show that 78% of the municipalities could have their basic energy needs and 18% of the demand for productive uses met by crop residues and silviculture production. For the state of Minas Gerais, with its tradition of agriculture, biomass residual energy is viable and should be considered by policymakers.